IL-33-ST2 Axis in Liver Disease: Progression and Challenge. (18th October 2017) - Sun, Zijian; Chang, Binxia; Gao, Miaomiao; Zhang, Jiyuan; Zou, Zhengsheng
Abstract : The new member of the IL-1 family, interleukin-33 (IL-33), participates in the progression of a variety of diseases through binding with its receptor ST2. Recently, much clinical evidence and experimental data have indicated that IL-33 is associated with various liver diseases. This review primarily addresses the relationship between IL-33 and several hepatic diseases. IL-33 can alleviate high-fat diet- (HFD-) induced hepatic steatosis and insulin resistance, and IL-33 acts as an alarmin, which quickly triggers the immune system to respond to virus invasion and toxic damage to the liver. However, when liver injury is chronic, IL-33 promotes Th2 reactions and hepatic stellate cell (HSC) activity, facilitating progression to liver fibrosis. The complicated functions of IL-33 should be considered before its clinical application.